2017
DOI: 10.12688/f1000research.10041.1
|View full text |Cite
|
Sign up to set email alerts
|

Expresso: A database and web server for exploring the interaction of transcription factors and their target genes in Arabidopsis thaliana using ChIP-Seq peak data

Abstract: Motivation: The increasing availability of chromatin immunoprecipitation sequencing (ChIP-Seq) data enables us to learn more about the action of transcription factors in the regulation of gene expression. Even though in vivo transcriptional regulation often involves the concerted action of more than one transcription factor, the format of each individual ChIP-Seq dataset usually represents the action of a single transcription factor. Therefore, a relational database in which available ChIP-Seq datasets are cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“… c ChIPBase v2.0: http://rna.sysu.edu.cn/chipbase/ (9). d Expresso: http://bioinformatics.cs.vt.edu/expresso/ (10). e ReMap 2018: http://remap.cisreg.eu (5).…”
Section: Application and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… c ChIPBase v2.0: http://rna.sysu.edu.cn/chipbase/ (9). d Expresso: http://bioinformatics.cs.vt.edu/expresso/ (10). e ReMap 2018: http://remap.cisreg.eu (5).…”
Section: Application and Discussionmentioning
confidence: 99%
“…For plant species, there are several databases devoted to collecting plant ChIP-seq data and identifying their gene regulation mechanisms. For example, Expresso was created to identify the regulatory relationships among 20 A. thaliana TFs and their target genes from public ChIP-seq data (10). PlantTFDB 4.0 is a useful TF repository for green plants, providing various information leading to an understanding of the functions of TFs as well as genome-wide regulatory maps for 14 TFs (8).…”
Section: Application and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green and red arrows represent activation and repression, respectively. access available processed ChIP-seq data in Arabidopsis (Aghamirzaie et al, 2017).…”
Section: Experimental Methodologies To Generate Gene Regulatory Networkmentioning
confidence: 99%
“…The reduced photo-inducibility of these two genes in PIF3 antisense transgenic plants confirms the view that phytochrome signals are targeted directly to the promoters of light-inducible genes through PIF3. Aghamirzaie et al ( 2017 ) reported that Acyl-CoA oxidase (At4g16760) in the upstream MVA pathway, and sterol 4-alpha-methyl-oxidase 2-1 (At1g07420) contain PIF3 binding sites in their promoters by ChIP-chip.…”
Section: Introductionmentioning
confidence: 99%